The Influence of Perceived Trust, Perceived Ease of Use, Perceived Benefits, Perceived Risk, Perceived Service Quality and WOM on Interest in Using Mobile Banking at BUMN Bank - Nurlaila, Nurlaila; Murtiasih, Sri (International Journal of Social Science, Education, Communication and Economics, 2023)
This research was conducted with the aim of measuring perceptions of trust, perceived ease of use, perceived benefits, perceived risks, perceived service quality and positive of mouth (WOM) on online customer interest using the Structual Equation Model (SEM) method. This type of research is descriptive quantitative. Data collection techniques use questionnaires, observation and documentation. The sample used was 243 respondents. The data analysis technique uses Structual Equation Model (SEM) analysis with the help of SmartPLS version 3. The research results show that perception of trust, perception of risk and perception of service quality have no effect on interest in using this mobile banking application, in fact it does not always go hand in hand with customer enthusiasm (interest). BRI, BNI, BTN and Mandiri banks in Bekasi City. Perception of user convenience greatly influences interest in using Mobile Banking at BRI, BNI, BTN and Mandiri Banks in Bekasi City. Perceived benefits influence interest in using Mobile Banking at BRI, BNI, BTN and Mandiri Banks in Bekasi City. Word of Mouth (WOM) influences interest in using Mobile Banking at BRI, BNI, BTN and Mandiri Banks in Bekasi City